ANALISIS DETERMINAN INTERNET FINANCIAL REPORTING PADA PERUSAHAAN SYARIAH DI INDONESIA - Sari, Riske Cindy Permata; Alfian, Ahmad Hijri (LPPM University 17 Agustus 1945 Samarinda, 2025)
The objective of this riset is to investigate how elements such as company size, profitability, kemudian length of listing on the Indonesia Stock Exchange influence IFR procedures. This riset employs a quantitative methodology, selecting firms from diverse sectors through purposive sampling. Multiple linear regression is used for data examination. No statistically meaningful link exists between company size, profitability, kemudian IFR, though a negative association is observed with the duration of listing. This may be due to more established corporations holding a strong market reputation, making them less likely to engage in online financial disclosure. This empirical investigation offers insights into the connections between online financial reporting and specific corporate traits within the Indonesian business environment. It also highlights the need to consider other non-financial and governance-related factors when analyzing IFR practices. Keywords : Internet Financial Reporting, firm size, profitability, listing age, financial disclosure, Indonesia Stock ExchangeThe objective of this riset is to investigate how elements such as company size, profitability, kemudian length of listing on the Indonesia Stock Exchange influence IFR procedures. This riset employs a quantitative methodology, selecting firms from diverse sectors through purposive sampling. Multiple linear regression is used for data examination. No statistically meaningful link exists between company size, profitability, kemudian IFR, though a negative association is observed with the duration of listing. This may be due to more established corporations holding a strong market reputation, making them less likely to engage in online financial disclosure. This empirical investigation offers insights into the connections between online financial reporting and specific corporate traits within the Indonesian business environment. It also highlights the need to consider other non-financial and governance-related factors when analyzing IFR practices. Keywords : Internet Financial Reporting, firm size, profitability, listing age, financial disclosure, Indonesia Stock Exchange